Fostering Pre-Service Physics Teachers' Pedagogical Content Knowledge Regarding Digital Media - Rike Große-Heilmann; Josef Riese; Jan-Philipp Burde; Thomas Schubatzky; David Weiler (MDPI AG, 2022)
Since the use of digital media opens new possibilities in physics education, pre-service teachers should develop pedagogical content knowledge (PCK) regarding digital media during teacher education. In the joint project DiKoLeP (German for: digital competencies of pre-service teachers in physics) of RWTH Aachen University, the University of Graz and the University of Tübingen, we therefore developed and implemented a university teaching concept with certain core elements to foster this digital-media PCK of pre-service physics teachers. The teaching concept was implemented as a university seminar at the three universities, considering the common core elements as well as individual curricular requirements. We evaluated the teaching concept in a pre-post-design with a recently developed knowledge test to measure digital-media PCK. Our findings indicated that the developed knowledge test is suitable to validly measure the digital-media PCK of pre-service physics teachers. Furthermore, first results of the empirical evaluation at the three participating universities showed a significant increase in students' digital-media PCK with a small-to-medium effect for students who attended the theoretical as well as the practical sessions of the seminar.